Rainbow Chicks - Forming the Good Habit of Keeping Clean - Taking a Bath - Animation, TThunDer (Saga Egmont, 2022)
Jump in, have a nice warm bubbly bath!The Rainbow Chicks are going to have a bath, but the dirty Kiwi is not too keen on getting in. What\'s going on? Through this story, the Rainbow Chicks encourage children to enjoy bath time and form good hygiene habits. Through heart-warming stories, you experience the growth process of the Rainbow Chicks, by focusing on six EQ emotional intelligence, sense of responsibility, self-confidence, problem-solving ability, social skills and concentration. The stories guide children to embrace their emotions, care for, respect and tolerate others and take initiative to solve problems.